Development of a 2-D Motion Tracker Application Project Assisted By Computer Vision to Enhance Student’s Laboratory Skills - Zulkarnain Zulkarnain; N. W. S Darmayanti; L.S Utami; Johri Sabaryati; M. Isnaini (AL-ISHLAH: Jurnal Pendidikan, 2024)
The traditional lecture method, often utilized in classrooms, may limit the optimal learning experiences of students, confining their understanding to merely the theory and concepts of projectile motion. This study introduces a projectile motion tracker application as an innovative educational tool, aiming to enrich the physics learning process by enhancing students' laboratory skills. Employing a research and development (RD) approach, the study follows the 4-D model (Define, Design, Develop, and Disseminate) to create and evaluate the application. Data were collected from 74 high school students through pre- and post-tests to measure the improvement in their laboratory skills after using the application. The evaluation utilized questionnaires and tests, indicating that the application meets high standards in language, visual design, and software engineering according to expert assessments and ranks highly in practicality for both teachers and students. The practicality was evaluated based on ease of use, attractiveness, efficiency, and usefulness. Significantly, the application has proven to enhance students' laboratory skills, as evidenced by the improvement in pre-and post-test results. Therefore, the projectile motion tracker application project emerges as a viable alternative for educators at various levels to support and invigorate physics education.